The implementation of moderate religious education for students at state senior high school 13 oku, south sumatra - Azwar Aripin; Rahma Dewi Masithoh; Reza Fahlepi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to examine the implementation of religious moderation education in the environment of SMA Negeri 13 OKU. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation studies. The results of the study indicate that the values of religious moderation have been integrated into the learning process and extracurricular activities. The principal and Islamic Religious Education teachers show a strong commitment to fostering an attitude of tolerance and mutual respect among students. However, this study also found several obstacles, including differences in the background of students' religious understanding, teachers' limited understanding of the principles of moderation, and the influence of social media which sometimes facilitates exposure to radical narratives. These findings emphasize the importance of a holistic and collaborative approach in the implementation of religious moderation education. Schools, families, and communities need to work together to create an educational ecosystem that supports the internalization of moderation values in the younger generation. Religious moderation education is a strategic effort in building the character of students who are inclusive, tolerant, and ready to face the challenges of the times. This study is expected to provide practical and theoretical contributions in strengthening religious moderation programs in high schools.